Sonographycally guided hydrostatic reduction of childhood intussusception - Vidmar, Dubravka (Radiology and oncology (Ljubljana), 2004)
Background. Intussusception is the most common cause of bowel obstruction in children under two years of age. The proximal part of the bowel and its mesentery (the intussusceptum) enter within that part immediately beneath it (the intussuscipiens). Being pulled by peristalsis the mesenterial vessels getcompressed which result in ishaemia of the bowel wall. Most intussusceptions are ileocolic. The diagnosis can be confirmed by a contrast enema or ultrasound. Sonography demonstrates a so-called target-within-a-target patfern (in cross-section) with thickened edematous bowel wall with or without vascularisation and prestenotic dilatation with increased peristalsis. Therapeutic reduction can be attempted by a contrast enema (following diagnostic procedure) or by air, both under fluoroscopic monitoring, or by normal saline under sonographic guidance. Patients and methods. We detected sonographically intussusception in three girls of 15, 16 and 18 months having typical clinical signs. We continued with hydrostatic reduction under the sonographic guidance. The reduction was attempted with a saline enema on body-temperature, introduced by the equipment for contrast enema. The bottle o f normal saline was hung up 1 m over the examination desk.We needed few liters of saline to replace lost liquids due to the incomplete occlusion of rectum. Meanwhile we monitored the moving of the intussusceptum back into the proximal direction. Criteria for a succesful reduction were the disappearance of the intussusceptum and the passage of fluid through the ileocecal valve. Results. Success was proven in all three girls. No complications occured and the pain relieved immediately after the procedure. There were no signs of intussusception on sonography after 2 and 12hours. We saw a slightly edematous wall of ileocecal valve and terminal ileum. Due to their exellent clinical conditions they were discharged from hospital after a second sonography. (Abstract truncated at 2000 characters).
Keywords: baby; child; črevesje; črevesne bolezni; Diagnosis; Dojenček; Hidrostatski pritisk; Hydrostatic Pressure; Infant; Intussusception; Intususcepcija; invaginacija; otroci; Therapy; Treatment Outcome; Ultrasonography; zdravljenje; Zdravljenje, izid